2019
DOI: 10.3390/genes10070522
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Proteome Analysis and Identification of Fertility-Associated Biomarkers in Unexplained Male Infertility

Abstract: Up to 30% of men with normal semen parameters suffer from infertility and the reason for this is unknown. Altered expression of sperm proteins may be a major cause of infertility in these men. Proteomic profiling was performed on pooled semen samples from eight normozoospermic fertile men and nine normozoospermic infertile men using LC-MS/MS. Furthermore, key differentially expressed proteins (DEPs) related to the fertilization process were selected for validation using Western blotting. A total of 1139 and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 43 publications
5
31
0
Order By: Relevance
“…Earlier proteomic studies have reported the alteration of mitochondrial proteins in oxidative stress-mediated male infertility [45,58,59]. Underexpression of the mitochondrial proteins were especially prominent in unexplained male infertility cases [44]. In our proteomics study, we have observed a state of underexpressed mitochondrial proteins in spermatozoa of idiopathic male infertility cases and their expression increased significantly after oral intake of ‘FH PRO for Men’ for a period of six months (Table 2).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Earlier proteomic studies have reported the alteration of mitochondrial proteins in oxidative stress-mediated male infertility [45,58,59]. Underexpression of the mitochondrial proteins were especially prominent in unexplained male infertility cases [44]. In our proteomics study, we have observed a state of underexpressed mitochondrial proteins in spermatozoa of idiopathic male infertility cases and their expression increased significantly after oral intake of ‘FH PRO for Men’ for a period of six months (Table 2).…”
Section: Discussionsupporting
confidence: 61%
“…Any defect in the structure or composition of sperm proteins negatively affects its functions such as capacitation, hyperactivation, acrosome reaction and fertilization [18]. Several proteomic studies have demonstrated that the proteins involved in the vital function pathways or protein modification pathways of spermatozoa were dysregulated in male infertility conditions [20,29,44,45,46,47]. In the antioxidant (‘FH PRO for Men’) treated group, we noticed that the majority of the proteins, specifically chaperones and their associated factors that are involved in stabilization of protein function, were overexpressed (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant expression of sperm proteins was reported to affect the molecular mechanisms associated with motility, capacitation, acrosomal reaction, and sperm-oocyte interaction in unexplained male infertility cases [83]. For example, the proteins involved in chromatin assembly were defective in unexplained male infertility patients [84][85][86]. However, these findings require clinical validation.…”
Section: Proteins-sperm Proteomementioning
confidence: 99%
“…Male-factor infertility is thereby assumed to contribute to about half of the cases, although the actual causes remain unexplained in 30-50% of the men seeking medical help [Poongothai et al, 2009;Nieschlag et al, 2010;Massart et al, 2012;Hamada et al, 2013;Krausz and Riera-Escamilla, 2018;Ferlin et al, 2019]. In fact, the main biomarker for male sub-and infertility, semen analysis, cannot reliably discriminate fertile from infertile individuals [Kovac et al, 2013;Bracke et al, 2018;Cariati et al, 2019;Panner Selvam et al, 2019], and genetic analysis continues to be ineffective to date [Aston, 2014;Coutton et al, 2015;Song et al, 2016;Mitchell et al, 2017;Cariati et al, 2019]. On the other hand, clarification of the genetic causes is a prerequisite for developing a tailored therapy of male fertility impairment [Sullivan, 2004;Bonache et al, 2012].…”
mentioning
confidence: 99%